Labor exports from Palestine to Israel: A boon or bane for the West Bank economy? - Johanes Agbahey; Khalid Siddig; Harald Grethe; Scott McDonald (IZA Journal of Labor Policy, 2020)
This article analyzes the effects on the West Bank economy of temporary Palestinian employment in Israel, using a new database and a computable general equilibrium model. The results show that Palestinian employment in Israel increases household incomes but distorts the operation of the West Bank labor market and increases domestic wages. Employment in Israel increases the real exchange rate of the West Bank leading to "Dutch disease" effects that inhibit the development of the West Bank economy. A decrease in the number of Palestinian workers in Israel reduces household welfare, and constraints on the West Bank economy restrict domestic absorption of the extra labor. Hence, the Palestinian National Authority may seek more labor exports to Israel. This article contributes to the broader discussion on the effects of migration policies on labor-sending economies by demonstrating the nontrivial benefits from labor migrations, but that these benefits come with costs. This article explores policy options for offsetting those costs.
Keywords: D58; E16; E24; F51; J61; 330; labor market; unemployment; development policy; general equilibrium model; Palestine